Bilateral Effects of Unilateral Cochlear Implantation in Congenitally Deaf Cats - O'Neil, Jahn N. (2010)
Congenital deafness results in synaptic abnormalities in auditory nerve endings. These abnormalities are most prominent in terminals called endbulbs of Held, which are large, axosomatic synaptic endings whose size and evolutionary conservation emphasize their importance. Transmission jitter, delay, or failures, which would corrupt the processing of timing information, are possible consequences of the perturbations at this synaptic junction. We sought to determine whether electrical stimulation of the congenitally deaf auditory system via cochlear implants would restore the endbulb synapses to their normal morphology. Three and 6-month-old congenitally deaf cats received unilateral cochlear implants and were stimulated for a period of 10–19 weeks by using human speech processors. Implanted cats exhibited acoustic startle responses and were trained to approach their food dish in response to a specific acoustic stimulus. Endbulb synapses were examined by using serial section electron microscopy from cohorts of cats with normal hearing, congenital deafness, or congenital deafness with a cochlear implant. Synapse restoration was evident in endbulb synapses on the stimulated side of cats implanted at 3 months of age but not at 6 months. In the young implanted cats, post-synaptic densities exhibited normal size, shape, and distribution, and synaptic vesicles had density values typical of hearing cats. Synapses of the contralateral auditory nerve in early implanted cats also exhibited synapses with more normal structural features. These results demonstrate that electrical stimulation with a cochlear implant can help preserve central auditory synapses through direct and indirect pathways in an age-dependent fashion.